2000
DOI: 10.1096/fasebj.14.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of myostatin expression during modified muscle use

Abstract: Previous findings have provided strong evidence that myostatin functions as a negative regulator of muscle mass during development and growth. In the present study, we test the hypothesis that myostatin may serve a similar function in fully differentiated muscle experiencing modified loading. Our findings show that myostatin expression can be modulated in fully differentiated, nonpathological skeletal muscle in a manner that is inversely related to changes in muscle mass. Atrophy of rat hind limb muscles induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
166
2
11

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(194 citation statements)
references
References 34 publications
15
166
2
11
Order By: Relevance
“…[9][10][11] Increases in GDF-8 expression have been observed in conditions of muscle atrophy and/or dystrophy, while the GDF-8 mRNA is modified in response to muscle loading after atrophy. 12 To explore Foxo-1 as a potential molecular target for muscle wasting conditions and gain insight of the mechanism of Foxo-1 regulation of muscle development and growth, we used a modified RNA oligonucleotide targeting the Foxo-1 mRNA in muscle cells and in normal and cachectic mice. Our studies demonstrated that the modified RNA oligonucleotide could decrease the expression of Foxo-1 in cells and in vivo, leading to an increase in muscle weight.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11] Increases in GDF-8 expression have been observed in conditions of muscle atrophy and/or dystrophy, while the GDF-8 mRNA is modified in response to muscle loading after atrophy. 12 To explore Foxo-1 as a potential molecular target for muscle wasting conditions and gain insight of the mechanism of Foxo-1 regulation of muscle development and growth, we used a modified RNA oligonucleotide targeting the Foxo-1 mRNA in muscle cells and in normal and cachectic mice. Our studies demonstrated that the modified RNA oligonucleotide could decrease the expression of Foxo-1 in cells and in vivo, leading to an increase in muscle weight.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that MSTN could inhibit myogenesis and promote atrophy of adult skeletal muscle by suppressing proliferation of satellite cells [17] . However, other studies supported that the role of MSTN was to inhibit hypertrophy of skeletal muscle rather than to induce atrophy [11,18,19] . Our previous studies showed that there was an apparent association between MSTN expression and rat sciatic nerve injury [12,13] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that 10 days of hindlimb unloading causes a 16% atrophy in rat plantaris muscle with a 110% and 37% increase in MSTN mRNA and protein level, respectively. However, 30 min daily muscle loading during the unloading period helps prevent significant loss of muscle mass, despite a concomitant 55% increase in myostatin mRNA expression [11] . We have previously described expression pattern profile of rat MSTN in response to muscle atrophy induced by sciatic nerve injury [12,13] .…”
Section: Introductionmentioning
confidence: 99%
“…Myostatin knockout mice deposit two-to three-fold greater muscle mass than their wild-type littermates due to increase in both muscle fibre number (hyperplasia) and the fibre cross-sectional area (hypotrophy) (McPherron et al, 1997) during embryonic and early postnatal development (Wehling et al, 2000;Whittemore et al, 2003). A disruption of myostatin function by transgenic expression of its propetide (the 5 0 region, 866 nucleotides) was reported to result in significant muscle growth (Yang et al, 2001).…”
Section: Discussionmentioning
confidence: 99%